Meta Analysis of the Effect of Story Based Audio-Visual Media on Elementary School Students' Listening Skills - Intan Purnama Dewi; Setiawan Edi Wibowo; Mar'atu Zahra (FKIP - Universitas Riau, 2026)
Listening skills are a basic competency that plays an important role in the learning success of elementary school students. However, various studies show that students' listening skills are still relatively low, so effective learning media innovations are needed, one of which is through story based audio-visual media. This study aims to synthesize empirical evidence regarding the effect of story based audio-visual media on the listening skills of elementary school students using a meta-analysis approach. Articles were searched based on the PRISMA 2020 guidelines through Google Scholar and other indexed databases with a publication range of 2015–2025. Of the 5,000 articles identified, eight studies met the inclusion criteria after undergoing duplication screening, variable suitability, and full-text review. Data analysis was performed using the JASP application version 0.95.1.0 with calculations of Hedges' g effect size, heterogeneity, publication bias, and sensitivity analysis. The meta-analysis results showed a combined effect size of 1.576 (CI –0.384 to 3.537), which is classified as high. The heterogeneity value was very large (I² = 92.02%), so a random effects model was used. Overall, story-based audio-visual media has strong potential to improve listening skills in elementary school students, although its effectiveness is influenced by the context and design of the intervention.